Analysis of Mutational Profile of Hypopharyngeal and Laryngeal Head and Neck Squamous Cell Carcinomas Identifies KMT2C as a Potential Tumor Suppressor - Machnicki, Marcin M.; Rzepakowska, Anna; Janowska, Joanna I.; Pepek, Monika; Krop, Alicja; Pruszczyk, Katarzyna; Stawinski, Piotr; Rydzanicz, Malgorzata; Grzybowski, Jakub; Gornicka, Barbara; Wnuk, Maciej; Ploski, Rafal; et al. (Frontiers in Oncology, 2022)
Hypopharyngeal cancer is a poorly characterized type of head and neck squamous cell carcinoma (HNSCC) with bleak prognosis and only few studies focusing specifically on the genomic profile of this type of cancer. We performed molecular profiling of 48 HPV (Human Papilloma Virus)-negative tumor samples including 23 originating from the hypopharynx and 25 from the larynx using a targeted next-generation sequencing approach. Among genes previously described as significantly mutated, TP53, FAT1, NOTCH1, KMT2C, and CDKN2A were found to be most frequently mutated. We also found that more than three-quarters of our patients harbored candidate actionable or prognostic alterations in genes belonging to RTK/ERK/PI3K, cell-cycle, and DNA-damage repair pathways. Using previously published data we compared 67 hypopharyngeal cancers to 595 HNSCC from other sites and found no prominent differences in mutational frequency except for CASP8 and HRAS genes. Since we observed relatively frequent mutations of KTM2C (MLL3) in our dataset, we analyzed their role, in vitro, by generating a KMT2C-mutant hypopharyngeal cancer cell line FaDu with CRISPR-Cas9. We demonstrated that KMT2C loss-of-function mutations resulted in increased colony formation and proliferation, in concordance with previously published results. In summary, our results show that the mutational profile of hypopharyngeal cancers might be similar to the one observed for other head and neck cancers with respect to minor differences and includes multiple candidate actionable and prognostic genetic alterations. We also demonstrated, for the first time, that the KMT2C gene may play a role of tumor suppressor in HNSCC, which opens new possibilities in the search for new targeted treatment approaches.